Nominalization in The Psychology of Money Book by Morgan Housel - Jalilah, Elah; Zewitra (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
The study intends to investigate the use of nominalization in The Psychology of Money book by Morgan Housel. Specifically, the purposes of this study are to (1) identify the types of nominalization used in â€œThe Psychology of Moneyâ€ book, and (2) identify the types of suffixes used to form the nominalization. The qualitative method was employed to explain the types of nominalizations using Hallidayâ€™s theory and the types of suffixes using Quirkâ€™s theory. The data of this analysis were obtained from the first ten chapters of The Psychology of Money book. The results show that there are 864 nominalization words used in the book. The most dominant type (737 cases) is verb-to-noun nominalization and the rest (127 cases) is adjective-to-noun. All types of suffixes are used to create the formation of both verb-to-noun and adjective-to-noun. The findings contribute to enriching the knowledge of grammar, especially nominalization. Besides, it practically can be used for teaching and writing references.